GENETIC VARIATION AND EFFECTIVE POPULATION SIZE IN Dipteryx alata PROGENIES IN PEDERNEIRAS, SAO PAULO, BRAZIL - Santos, Wanderley dos [UNESP]; Aguiar, Ananda Virginia; Lemos Souza, Danilla Cristina [UNESP]; Torres Dini, Diego Gabriel [UNESP]; Souza, Francine Beatriz de [UNESP]; Dalastra, Cleiton [UNESP]; Rabelo Machados, Jose Arimateia; Sousa, Valderes Aparecida de; Teixeira de Moraes, Mario Luiz [UNESP]; Menezes Freitas, Miguel Luiz; Sebbenn, Alexandre Magno (Univ Federal Vicosa, 2018)
Genetic and phenotypic parameters of fork (BIF), stem form (RET) and diameter at breast height (DBH) for Dipteryx alata provenances and progenies were assessed. The trial was lead in a randomized block design, with 43 treatments (26 and 17 progenies from the municipalities of Tres Lagoas and Brasilia in the state of Mato Grosso do Sul and Distrito Federal, Brazil, respectively) and five plants per plot. The spacing between plants was 3 x 3 meters. The data analysis was performed using the REML/BLUP method (restricted maximum likelihood best linear unbiased prediction). Significant differences were detected between progenies only for DBH. The individual genetic values ranged from 3.7 to 21.7 % for BIF and DBH; genetic variation among progenies ranged from 9 to 10.5 % for BIF and DBH among provenances. Individual heritability in the strict sense was high for DBH (minimum from 0.31), revealing the potential for genetic improvement. Provenance and progenies trial showed genetic variability which can be exploited in forest improvement programs with a broad genetic base.
Keywords: Tropical trees; Ex situ conservation; Quantitative genetics